DO PACTO NACIONAL À GLOBALIZAÇÃO: ESTADO E SINDICATO NA REGULAÇÃO DO CAPITALISMO NORTE-AMERICANO (Revista de História Regional, 2007)
In the 1930s, the State and the unions in the United States begun a pro-cess of deep transformations that would allow them, in the next decades, to play central roles in the regulation of the American capitalism. However, both of them were unable to build permanent institutions of social agreement, like a labor party or tripartite agencies. Therefore, the North-american keynesian fordism resulted less institucionalized than the European social-democrat ones and, in the 1960s, not the unions, but the civil rights movements, would play a central role in the American political arena. With the crisis of the keynesian fordism and the corpora-te and conservative offensive of the 1970s, along with the beginning of the globa-lization process, which weakened nationally circumscribed social agreements, American unions went through a process of defensivness, in which the fight for material gains were substituted by the maintenance of inadequate jobs.